The Concise Cambridge History of English Literature - Sampson, George; Churchill, R. C. ([S.l.] : Cambridge University Press, 2014)
Sampson's Concise History (first published in 1941) was a summary in readable form of the great Cambridge History with some personal touches by Sampson. The second edition had a substantial new chapter by R. C. Churchill on twentieth-century literature and appeared in 1961. This is a digital reprint of the 1970 edition, prepared by Mr Churchill, which provides a revision of the first thirteen chapters. Three very substantial chapters were added that had the effect of making this the only complete and up-to-date survey as of 1970 of world literature in English. The literature of the USA is surveyed in extenso and in its own right. The literatures in English of Ireland, India, Pakistan, Ceylon, Malaysia, Canada, Australia, New Zealand, the West Indies, South Africa and the predominately English-speaking African states are also treated. Students and general readers will find this a comprehensive and lively-minded survey, guide and reference book to the world's literature in the English language.
Keywords: English literature